Co‐ingestion of prescription drugs and alcohol in US adults aged 50 years or older. (8th July 2021) - Schepis, Ty S.; Ford, Jason A.; McCabe, Sean Esteban
Abstract: Objective: To examine prevalence of past‐month prescription drug misuse (PDM) and alcohol co‐ingestion and its correlates in adults age 50 or older. Methods: Data were from the 2015–2018 US National Survey on Drug Use and Health ( n = 35, 190). PDM‐alcohol co‐ingestion was defined as prescription opioid, tranquilizer/sedative, or stimulant misuse while "drinking alcohol or within a couple of hours of drinking." Co‐ingestion prevalence was estimated, and logistic and negative binomial regressions examined the sociodemographic, physical health, mental health, substance use, and substance use disorder (SUD) correlates of co‐ingestion. Results: Over 344, 000 adults aged 50 years or older (0.3%) engaged in past‐month PDM‐alcohol co‐ingestion, or 27.4% of those with past‐month PDM. Past‐month co‐ingestion was linked to greater past‐month alcohol use frequency and elevated adjusted odds ratios (aORs) for all examined substance use outcomes (e.g., non‐PDM SUD aOR = 21.8; 49.7% prevalence rate). The aOR for suicidal ideation was 506% higher in those with co‐ingestion than those without past‐year PDM. Conclusions: US adults aged 50 years or older with past‐month PDM‐alcohol co‐ingestion are at high risk for SUD and concerning mental health symptoms. Screening for mental health and substance use treatment is warranted among aging adults with signs of PDM, especially involving co‐ingestion.